Anxiety Sensitivity and Opioid Misuse among Opioid-using Adults with Chronic Pain - Rogers, Andrew H. (Am J Drug Alcohol Abuse, 2019)
BACKGROUND: The opioid epidemic is a significant public health crisis, and this problem is particularly prevalent among individuals with chronic pain. Accordingly, there is an urgent need for interventions to mitigate the risk for opioid misuse and opioid use disorder among people with pain. Given that mental health problems, specifically anxiety, are common among people who misuse opioids, it is important to examine factors that link mental health problems with opioid misuse to ultimately inform the development of novel interventions. Anxiety sensitivity, a transdiagnostic vulnerability factor, may be one important mechanism in elevated opioid misuse among persons with chronic pain. METHOD: Therefore, the current cross-sectional study examined anxiety sensitivity (and construct sub facets) as a predictor of opioid misuse among adults with chronic pain. RESULTS: Results indicated that anxiety sensitivity was associated with multiple aspects of opioid misuse, and the magnitude of effects ranged from medium to large. Results were observed over and above the variance accounted for by age, sex, income, education, perceived health, and pain severity. CONCLUSION: These findings suggest that future research should continue to explore the explanatory relevance of anxiety sensitivity in opioid misuse among individuals with chronic pain.